Recrudescence of Focal Stroke Symptoms during Pain Management with Hydromorphone - Bernstock, Joshua D.; Budinich, Craig S.; Cohen, Leonardo G.; Awosika, Oluwole O. (Frontiers in Neurology, 2016)
Abstract: Patients who have recovered from a prior stroke may experience a reemergence of their original stroke syndrome secondary to metabolic derangements, sedation, infection, and/or fatigue. Critically, the molecular/cellular mechanisms mediating symptom recurrence after exposure to analgesic agents remain unknown. Accordingly, herein we report a unique case of a patient with hydromorphone-induced recrudescence 30 years after her initial stroke event(s), and in so doing propose a putative mechanism related to post-infarction functional neuroplasticity.